A Critical Discourse Analysis of Gender Disparity in Taskmaster - Nauka Nayana Prasadini (ENLIT, 2021)
British comedy panel show is the television comedy genre that is known for spontaneous banters and humour. Despite the popularity, the shows in this genre are often criticized as "male-dominated" and heavily gender-biased. As one of the most popular comedy panel shows, Taskmaster also shows the same problems, despite having more women in the future series. Therefore, the study analyses the gender disparity as showed in Taskmaster through the perspective of Critical Discourse Analysis (CDA). The study uses a qualitative approach, focusing on CDA. Moreover, the data was taken from the Series 2 of Taskmaster using open coding technique and analysed with Fairclough’s Critical Discourse Analysis framework. The results show that throughout the series, the only woman panellist is often being underestimated and interrupted by men, confirming gender disparity in Taskmaster. She is also constantly being objectified while defending her attempts, as this occurrence increases throughout the episodes. Interestingly, some of the men panellists and presenters try to diminish the male-dominated nature by helping in weighing sexist-sounding tasks or decisions. This also confirmed the opinions that men often hold more power in comedy panel show than women.